THINK-PAIR-SHARE STRATEGY IN TEACHING READING AT THE SECOND SEMESTER STUDENTS OF IKIP MATARAM - I Made Permadi Utama (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2017)
This research was aimed to find out the effectiveness of using Think Pair Share (TPS) strategy in teaching reading at the second semester students of IKIP Mataram. Research design was quasi-experimental with nonequivalent control group design. The sample of the research was 79 students and it was taken by using cluster random sampling technique and the data gathering used multiple choice items that consist of 20 items. The data analysis used t-test formulation. Based on the data analysis, t-test score was 1.804 and t-table 1.664 with signification level 5% and degree of freedom N – 2 = 79 – 2 = 77. It means that t-test was higher than t-table (1.804 > 1.664). Therefore alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. So, there was significant effect of using Think Pair Share (TPS) strategy in teaching reading at the second semester students of IKIP Mataram.